Prolapsed fallopian tube to the vagina after hysterectomy a year ago: A case report - Yu-Hsuan Lin; Huang-Ping Shen; Chih-Jen Tseng; Liang-Ying Wu; Li-Hsin Hsia (Taiwanese Journal of Obstetrics & Gynecology)
Objective: This case report aims to present a rare occurrence of fallopian tube prolapse into the vaginal vault following hysterectomy, underscoring the importance of recognizing this uncommon complication. Case Report: A 45-year-old woman, with a history of hysterectomy for adenomyosis, presented with symptoms mimicking a vaginal tumor, including persistent discharge, abdominal pain, postcoital bleeding, and weight loss. Imaging raised concerns of malignancy, but surgery revealed a prolapsed fallopian tube with chronic inflammation. This case highlights the diagnostic challenges, with less than 100 reported instances. Differential diagnoses encompassed diverse pelvic pathologies, necessitating histological confirmation. Factors contributing to prolapse include poor vault closure and early sexual activity. Awareness of this complication is pivotal when evaluating post-hysterectomy symptoms, ensuring precise diagnosis and appropriate management. Conclusion: Fallopian tube prolapse into the vaginal vault is a rare post-hysterectomy complication. Early recognition and accurate diagnosis are essential for effective management of patients presenting with post-hysterectomy symptoms, such as vaginal bleeding and discharge.